Information Design for the Development of Aceh's Door Batik Pattern on Font Medium - Fauzi, Ahmad Nurzaeni; Wantoro; Salvina, Mauliza (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Aceh is one of the provinces in Indonesia. Aceh also has batik with its own distinctive motif. One of the most popular motifs is the Pintu Aceh motif, this motif adapts from existing motifs that are commonly found in typical Acehnese handicrafts. Although it’s popular, but still the lack of media introduction developed further to the maximum. In terms of visual, The Pintu Aceh motif has the potential to be a more interesting media. The purpose of this design is to introduce aceh’s batik Pintu Aceh motif culture in digital-based in order to adjust the development of the times and technology. Through this design, one of the introductions of Indonesian culture that can be accepted and recognized through the characteristics of Aceh Pintu Aceh batik motifs. This design was written using qualitative writing method, which is sourced from books, journals, or articles. To complete the data and references, the author also conducted research through questionnaires to reach the target audience, in order to know the opinions of the public about Aceh batik motifs Pintu Aceh, especially in the media of interesting introduction. Therefore, the design of this information is made through font media by adaptingthe character of Pintu Aceh batik motif. It’s hoped that this design can foster knowledge about Aceh batik motifs Pintu Aceh and be proud of the strength of Indonesian culture, especially Aceh.